Epidemiology of village chicken diseases: A longitudinal study on the magnitude and determinants of morbidity and mortality—The case of Newcastle and infectious bursal disease - Jarso, D. (Addis Ababa University, 2015)
A longitudinal study was carried out from September 2014 to May 2015 on village chicken of Lume district for the aim of determining incidence rate of mortality of Newcastle disease (NCD) and infectious bursal disease (IBD) and the associated risk factors. In addition in a retrospective survey past occurrence of these disease was assessed. Simple random sampling method was used to select the peasant associations (PAs) and the households. Owners and veterinary field workers perception on chicken diseases was collected from 120 respondents through structured questionnaire. The majority (75%) of the respondents put diseases as major causes of village chicken mortality, out of which 78.3% of the respondents indicated NCD locally known as “Fangle” as the leading disease that cause mortality of chicken in the village. Of the 1358 registered chicken, 202 (14.9%) survived the entire follow-up period. A total of 843 chickens found dead of NCD outbreak during the follow-up period. The general mortality rate was 62.1% whereas the incidence rate was 113.2 cases per 1000 chicken month. Over the duration of the study, serum samples of 521 chickens were collected to confirm the cause of the outbreak, 242 from sick and 279 from apparently health chicken. Serology using HAI and I-ELISA test were conducted to determine the seroprevalence of NCD and IBD, respectively. In total 28.6% (149/521) and 20.7% (108/521) were positive for NCD and IBD, respectively. Among the 242 sera collected from clinically diseased chicken 61.6% (149/242) and 38.4% (93/242) were positive for NCD and IBD, respectively. Statistically significant (p<0.05) difference in prevalence of NCD was found between highland and lowland; chicken flock size and sampling months. Statistically significant (p<0.05) difference in seroprevalence of IBD was found between different age groups; household flock size and sampling months. This study has shown that NCD and IBD are one of the major infectious diseases threatening the survival and productivity of traditionally managed local chickens in East Showa zone. Thus, routine vaccination program is recommended.